Principles of Enterprise Potential Management in the Coordinates System of Organizational Development - KNIAZ SVIATOSLAV; SOPILNYK LYUBOMYR; SHCHEBEL ANDRII; MOROZ SVITLANA; KALASHNYK OLENA; SKRYNKOVSKYY RUSLAN; KRAMAR MARIAN; SPITSYNA ANHELINA; KYRYCHENKO OLENA; GNYLIANSKA LESIA; LAKIZA VIKTORIIA (Communications of International Proceedings, 2020)
Enterprise potential management, as a specific function of management, is implemented by planning the development of enterprise potential, organizing the process of its formation and use, motivating management to rational use of enterprise potential, as well as controlling and regulating the formation and use of capacity. It should be recognized that despite the high level of formalization of the process-functional approach to managing the potential of the enterprise today the object of management is rather poorly formalized, namely - the potential of the enterprise. Due to the diversity of potentials there is a large number of types of their development. The article proposes a system of principles of capacity management in the coordinate system of organizational development. The list of principles is formed so as to level the diversity of potentials of the enterprise, and the coordinate system of organizational development is considered as one that integrates different types of development into one whole.
Keywords: Potential; Management; Organizational Development; Organizational Change; Enterprise.